Development of Removable Hollow Cathode Discharge Apparatus for Sputtering Solid Metals - Daisuke Ishikawa; Shuichi Hasegawa (Journal of Spectroscopy)
A hollow cathode discharge cell has been developed for a variety of sample phases. To make the experimental apparatus compact, we have adopted DC discharge, and the discharge cell was inexpensively constructed for replacement with commercially available vacuum parts. The most distinctive attribute of the developed cell is the double structure of the cathodes. The occurrence of sputtering resulted in the metal atom in gas phase. With Ar buffer gas, the favorable condition of laser absorption spectroscopy for the gas phase sample was investigated.